Zfp423/OAZ Mutation Reveals the Importance of Olf/EBF Transcription Activity in Olfactory Neuronal Maturation - Roby, Yang A. (Society for Neuroscience, 2012)
Zfp423/OAZ, a multi-zinc finger protein, is proposed to participate in neuronal differentiation through interactions with the Olf/EBF (O/E) family of transcription factors and mediate extrinsic BMP signaling pathways. These activities are associated with distinct domains of the Olf/EBF-associated zinc finger (OAZ) protein. Sustained OAZ expression arrests olfactory sensory neurons (OSNs) at an immature state and alters olfactory receptor expression, but the mechanism remains elusive. We show here that constitutive expression of a C-terminal mutant OAZ (OAZΔC) in mice that selectively disrupts OAZ–O/E interaction while retaining other activities, exhibits apparently normal OSN differentiation. Additionally, interfering with potential BMP signaling pathways by inducible Follistatin expression in adult mice does not alter the neuronal lineage or differentiation status. Our results indicate that O/E-mediated processes are essential for the differentiation of OSNs and the establishment of a mature phenotype. BMP signaling pathways, if they are active in normal adult olfactory epithelium, may play a minor role in this tissue.